2020
DOI: 10.3390/plants9010089
|View full text |Cite
|
Sign up to set email alerts
|

Lobularia maritima (L.) Desv. Aerial Parts Methanolic Extract: In Vitro Screening of Biological Activity

Abstract: Lobularia maritima (L.) Desv. is a perennial herb growing wild in the Mediterranean basin. The aim of this work was to assess the fatty acid, terpene, phytosterol, and phenolic composition of the methanolic extract and its sub-fractions using Gas Chromatography-Mass Spectrometry (GC-MS), High-Performance Liquid Chromathography with Dioide-Array Detector (HPLC-DAD), High-Performance Liquid Chromathography-High Resolution Mass Spectrometry (HPLC-HRMS), and Electrospray Ionization Tandem Mass Spectrometry (ESI-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
(67 reference statements)
0
12
1
Order By: Relevance
“…Our findings suggest that the roots have higher antioxidant potential than the aerial parts of the studied plant. Our results are much higher than those reported in a previous study that investigated the radical scavenging potency of Lobularia maritima methanol extracts from Tunisia with IC50 values equal to 253.81 ± 1.01 μg/mL and 937.70 ± 8.07 μg/mL, for the EtOAc fraction and the raw extract, respectively [33].…”
Section: Discussioncontrasting
confidence: 81%
“…Our findings suggest that the roots have higher antioxidant potential than the aerial parts of the studied plant. Our results are much higher than those reported in a previous study that investigated the radical scavenging potency of Lobularia maritima methanol extracts from Tunisia with IC50 values equal to 253.81 ± 1.01 μg/mL and 937.70 ± 8.07 μg/mL, for the EtOAc fraction and the raw extract, respectively [33].…”
Section: Discussioncontrasting
confidence: 81%
“…Available studies related to the bioactivity of this plant were mostly focused on plant extracts, rather than essential oils. Marelli et al [ 10 ] reported several important health benefits of the extracts of aerial Lobularia maritima (L.) Desv. parts.…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical screening indicates that L. maritima contains substances with high therapeutic value, such as fatty acids (capric, 9-oxononanoic, lauric, 14-methylpentadecanoic, palmitic, myristic, stearic, 16-methyloctadecanoic acid), terpenoids (dihydroactinidiolide, neophytadiene, betulinaldehyde, β -amyrin acetate, (+)-2-bornanone, and nootkaton-11,12-epoxide), and phytosterols ( β -sitosterol, 24-methylenecycloartanol, and tremulone) [ 118 , 119 , 120 ]. In addition, many compounds accumulated by L. maritima function as antioxidants, eliminating reactive oxygen species, but are also responsible for the antibacterial, anti-inflammatory, anticancer, antiobesity, and hepatoprotective properties of the raw plants [ 86 , 118 , 119 ]. This group includes flavonoids, anthocyanins, phenolic acids, and tannins, as well as essential oil compounds and macromolecules such as proteins and polysaccharides [ 119 , 120 , 121 , 122 ].…”
Section: Phytochemical Composition Of Halophytesmentioning
confidence: 99%
“…In addition, many compounds accumulated by L. maritima function as antioxidants, eliminating reactive oxygen species, but are also responsible for the antibacterial, anti-inflammatory, anticancer, antiobesity, and hepatoprotective properties of the raw plants [ 86 , 118 , 119 ]. This group includes flavonoids, anthocyanins, phenolic acids, and tannins, as well as essential oil compounds and macromolecules such as proteins and polysaccharides [ 119 , 120 , 121 , 122 ].…”
Section: Phytochemical Composition Of Halophytesmentioning
confidence: 99%